PENGARUH METODE GASING TERHADAP KEMAMPUAN BERHITUNG SISWA GANGGUAN PENDENGARAN KELAS V SDLB - Bagas Eka Ramadhan; Faiz Noormiyanto (STKIP Subang, 2026)
Hearing-impaired students often experience difficulties in learning mathematics, particularly in developing numeracy skills, due to limitations in receiving verbal information and understanding abstract mathematical concepts. Therefore, an instructional approach that emphasizes concrete, visual, and enjoyable learning experiences is needed. This study aimed to determine the effect of the GASING (Easy, Fun, and Enjoyable) method on the numeracy skills of fifth-grade students with hearing impairments at SLB B Karnnamanohara. The research employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest design. The participants consisted of seven fifth-grade students selected through saturated sampling. Data were collected using a numeracy achievement test administered before and after the implementation of the GASING method. The obtained data were analyzed using descriptive statistics, normality testing, linearity testing, and Paired Sample t-test. The findings indicated that the mean pretest score was 64.29, while the mean posttest score increased to 84.71. The improvement demonstrates that students' numeracy skills significantly increased after receiving instruction through the GASING method. Statistical analysis further confirmed a significant difference between pretest and posttest scores. These findings indicate that the GASING method effectively improves numeracy skills among students with hearing impairments by facilitating conceptual understanding through concrete, systematic, and enjoyable learning activities.